Parameters Affecting the Blast Performance of High Strength Fibre Reinforced Concrete Beams - Algassem, Omar (Université d'Ottawa / University of Ottawa, 2016)
A limited number of studies have been conducted in the literature in order to investigate the behaviour of high-strength fibre-reinforced concrete (HSFRC) structural components subjected to blast loads. This study summarizes the results of a research program investigating the potential of using steel fibres to improve the blast performance of high-strength reinforced concrete beams. As part of the experimental investigation twenty beams were tested, including nine beams tested under static four-point bending, and eleven beams tested under dynamic blast loads using a shock-tube. Parameters considered in the study include the effect of concrete strength, steel fibres, fibre content, fibre type, longitudinal reinforcement ratio, and presence of shear reinforcement. All beams in the study have identical dimensions, with a cross-section of 125 x 250 mm and length of 2440 mm. To manufacture the specimens, two beams were cast with normal-strength self-consolidate concrete (SCC), with a specified strength of 50 MPa, while the remaining beams were cast with either plain or fibre-reinforced high-strength concrete having a compressive strength which varied between 95-110 MPa. The steel fibre content in the HSFRC beams varied between 0.5 and 1.0%, by volume of concrete. To investigate the effect of reinforcement ratio (ρ), the beams were reinforced with 2-#4 (American size) bars, 2-15M bars or 2-20M bars (ρ = 1.02%, 1.59%, and 2.41%, respectively). The majority of the plain concrete beams had transverse reinforcement which consisted of 6 mm stirrups arranged at a spacing of 100 mm in the shear spans, while most of the HSFRC beams were built without stirrups. The results indicate that all the parameters in this study (reinforcement ratio, presence of stirrups, concrete strength, steel fibres, fibre content and fibre type) affected the static and blast response of the beams, however, the results demonstrate that steel fibres have a more remarkable effect when compared to the other parameters. The provision of fibres is found to improve the blast performance of the HSC beams by increasing shear capacity, reducing maximum and residual mid-span displacements, reducing blast fragments and increasing damage tolerance.
Keywords: Dynamic Test; Static Test; Steel fibre; Steel reinforcement ratio; Concrete type